Oxidative Removal of Volatile Organic Compounds over the Supported Bimetallic Catalysts - Zhiquan Hou; Wenbo Pei; Xing Zhang; Yuxi Liu; Jiguang Deng; Hongxing Dai (The Global Environmental Engineers, 2020)
Volatile organic compounds (VOCs) and methane are pollutants that are harmful to the atmosphere and human health. It is highly required to control emissions of VOCs. Catalytic oxidation is one of the most effective pathways for the elimination of VOCs, in which the key issue is the development of novel and high-performance catalysts. In this review article, we briefly summarize the preparation strategies, physicochemical properties, catalytic activities, and stability for the oxidative removal of VOCs of the supported bimetallic catalysts that have been investigated by our group and other researchers. The supported bimetallic catalysts include the supported noble bimetal, supported noble metal-transition metal, and supported non-precious bimetal catalysts. It was found that catalytic performance was related to one or several factors, such as specific surface area, pore structure, particle size and dispersion, adsorbed oxygen species concentration, reducibility, lattice oxygen mobility, acidity, reactant activation ability, and/or interaction between bimetals or between metal and support. The stability and ability of anti-poisoning to water, carbon dioxide or chlorine were related to the nature of the bimetal and support in the catalysts. In addition, we also envision the development trend of such a topic in the future work.